Rewiring lipid metabolism to enhance immunotherapy efficacy in melanoma: a frontier in cancer treatment - Xiong, Lihua; Cheng, Jian (Frontiers in Oncology, 2025)
Immunotherapy has transformed the landscape of melanoma treatment, offering significant extensions in survival for many patients. Despite these advancements, nearly 50% of melanoma cases remain resistant to such therapies, highlighting the need for novel approaches. Emerging research has identified lipid metabolism reprogramming as a key factor in promoting melanoma progression and resistance to immunotherapy. This reprogramming not only supports tumor growth and metastasis but also creates an immunosuppressive environment that impairs the effectiveness of treatments such as immune checkpoint inhibitors (ICIs). This review delves into the intricate relationship between lipid metabolism and immune system interactions in melanoma. We will explore how alterations in lipid metabolic pathways contribute to immune evasion and therapy resistance, emphasizing recent discoveries in this area. Additionally, we also highlights novel therapeutic strategies targeting lipid metabolism to enhance immune checkpoint inhibitor (ICI) efficacy.